A contemporary review of criminal responsibilities of directors of companies and the impact on corporate governance in Nigeria - Ogunlade, Femi Z. (African journal of law and criminology, 2023)
This paper examines the criminal liability of directors of company, being the alter ego directing the affairs of the company and carrying out corporate decisions. While noting that corporate criminal liability could be imputed to businesses including occasions where an employee acted within the scope and nature of his employment or the employee acting at least in part to benefit the corporation, or intent is imputed to the company or, where the criminal act is the policy of the company’s internal decision-making procedures, or where such an act is encouraged to be committed by the company , it is posited that the company should be held criminally liable in all respects for the conduct of individual employees except it is shown that the company has done everything within its power to prevent such misconduct. This paper considers artificial intelligence as it has opened a new vista as to the extent of liability of a company where crimes occurred through the use of automated machine or robotic technology. We conclude that the main legislation on crime prevention (Criminal Code, Penal Code and Administration of Criminal Justice Act) should have a clear provision for corporate criminal liability, while, persons in the criminal code should be expressly made to include companies, as this has not been interpreted clearly. This paper finds out that Nigerian criminal legislation failed to identify the offences that can be committed by corporate entities. Corporate crimes and misfeasance are more common than ever before, and it is still believed that prosecuting corporate bodies can be relatively challenging. Amendment of our criminal laws is therefore urged to promote good corporate governance and engender economic growth.